Symposium on the Kalahari Ecosystem summary and conclusions - A. J Hall-Martin (Koedoe: African Protected Area Conservation and Science, 1984)
This symposium has dealt largely with the Kalahari Gemsbok National Park (KGNP), an area which has been under the control of the National Parks Board of Trustees since 1931. The park, which covers some 9 600 km2 is part of an international conservation area which includes the adjoining 26 600 km2 Gemsbok National Park in Botswana and adjoining wildlife management areas.